Health Expenditure and Nigeria’s Economic Growth - OKOLIE, Ugo Chuks; FADEYI, Folarin Julius (Universitas Pendidikan Indonesia, 2023)
Using time series data from 1999 to 2022, this study examines the impact of health financing on economic growth in Nigeria. The findings indicate that the previous year's productive activities have a positive effect on economic growth in both the short and long run. The current domestic government general health expenditure has a negative growth effect on economic growth, whereas the previous year's domestic general government health expenditure has a positive growth effect on economic growth. Domestic private health spending has a significant positive effect on economic growth. As a result, the importance of private health spending over government health spending in improving economic growth is reinforced. Thus, it was determined that health financing is required for long-term economic growth. As a result, the government should increase individual health spending capacity, increase health sector budgetary allocation, and ensure prudent and effective health sector budgetary implementation.